PENGARUH PENUNDAAN PEMERIKSAAN URIN TERHADAP JUMLAH LEUKOSIT PADA PENDERITA INFEKSI SALURAN KEMIH - I Gusti Agung Dewi Sarihati; Bunga Dewanti; Burhannuddin Burhannuddin (Meditory : The Journal of Medical Laboratory, 2019)
Abstract. Urine is the rest of the body's metabolism that is released through the process of urinalization. Urine examination aims to determine the condition of the kidney and other urinary tracts. Delays in examinations in the laboratory often occur resulting in disturbed urine stability. This study aims to determine the effect of delays on the number of urine leukocytes in patients with urinary tract infections. This research with posttest only control group design using four control and treatment groups each consisting of 9 samples. The control group is the result of urine examination which is examined before 30 minutes while the treatment group is the result of urine examination after 1, 2 and 3 hours since being collected. The results showed an average difference between the control and treatment groups, especially there was a significant reduction in the 3-hour delay group.Keywords: urine leukocytes, delay in urine examination